Answer:
![x^2-y^2=-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/65msp0ejot7elo9frrwcj3kozfqybvc5z9.png)
Explanation:
The problem tells us that the slope of the tangent to a curve at any point
on the curve is x divided by y, that is:
![m=(x)/(y)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tf0a0mwfhb25kku27es1h0rb0b2fk1qulq.png)
We also know that the point
is on the curve. By taking a look on the options this point lies on both equations, namely:
![x^2+y^2=13 \ because \ (2)^2+(-3)^2=13 \\ \\ x^2-y^2=-5 \ because \ (2)^2-(-3)^2=-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3do83w8du2ckx20u5az3qp7ina2sl7op6i.png)
We know that the derivative is the slope of the tangent line to the graph of the function at a given point. So taking the derivative of both equations we have:
![(d)/(dx)(x^2+y^2)=(d)/(dx)(13) \\ \\ \therefore 2x+2y(dy)/(dx)=0 \\ \\ \therefore m=(dy)/(dx)=-(x)/(y)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2gkr0vrzmh0u47m3qchf9i2q0ooa73gs54.png)
And:
![(d)/(dx)(x^2-y^2)=(d)/(dx)(-5) \\ \\ \therefore 2x-2y(dy)/(dx)=0 \\ \\ \therefore m=(dy)/(dx)=(x)/(y)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yrkhdy04bxjr2de48kyattskecexk0d4b5.png)
So
also meets the requirement of the condition the slope of the tangent to a curve at any point (x, y) on the curve is x divided by y. Therefore this is the correct option.